Cytotoxic Activity of Parmelia perlata Extracts against Artemia Salina - Mayilsamy, M.; Geetharamanan, K. (Journal of Experimental Sciences, 2016)
The brine shrimp lethality bio assay represents a rapid, inexpensive and simple bioassay for testing plant extracts bioactivity which in most cases correlates reasonably well with cytotoxic and antitumor properties. The assay is considered to be a very useful tool for preliminary assessment of toxicity. In the present study the lichen Parmelia perlata was extracted with solvents of varying polarity such as hexane, ethyl acetate, acetone and methanol and tested for hatch inhibition of cysts of Artemia salina and cytotoxic activities against Artemia salina naupilii. The highest cytotoxic potential among all the plant extracts tested was explored from the hexane extract of P. perlata which showed 100% brine shrimp mortality at 100ppm. The least activity among all the plant extracts was found in the methanol extract ofÂ  P. perlata.